Ngāti Hotu in Paradise: How Contemporary Hotu in Aotearoa New Zealand Defend their White Pre-Polynesian Settlement Theory - Galbraith, Deane (Journal of the bible and its reception, 2025)
A group of perhaps 2,000 Māori, whose main representative is Monica Matāmua, claim that they are not Māori or Polynesian but descendants of a White race they call the Hotu. They claim that they were the first to settle in Aotearoa New Zealand, more than a thousand years before Māori, so that they are the true Indigenous inhabitants of the land. Further, they hold to a conspiracy theory that claims evidence for White Hotu has been covered up by Māori and elites. This article examines the epistemic modes by which modern Hotu defend their contentions. A key foundation is their employment of the biblical motif of Paradise, by which they identify as an originally Edenic people, in contrast to Māori. The Hotu combine the authoritative biblical motif of Paradise with parallel epistemic foundations, including Māori traditions of original peoples, the colonial myth of a Pacific Paradise, and modern DNA testing. This article demonstrates how the Hotu generate epistemic authority not only via each epistemic mode, but via a hermetic-like combination of epistemic modes. The piling up of superficially similar epistemic claims provides a seemingly profound yet spurious basis for asserting White pre-Polynesian identity and origins. It also provides Hotu with a sense of agency that encourages their ongoing fight to reverse the damaging effects of colonization. Yet the Hotu contention to be descendants of a White pre-Polynesian people comes at the significant cost of demonizing Māori, absolving European colonizers, and emboldening many New Zealanders to deny Māori their Indigenous status.